(untitled) (Research, Society and Development, 2022)
In Brazil, as in other developing countries, intestinal parasites are a serious public health issue. Preschool children deserve special attention regarding intestinal parasite infection since this group has a higher risk of mortality for several infections. In addition, the healthcare in this age group can increase its chances of reaching school-age and adulthood. This paper aims to develop fun activities to prevent infection by intestinal parasites, especially focusing on hand washing, with children of a daycare placed at Niterói-RJ, inspired by experience exchange. Through the infants comments and behaviour, it was possible to notice that their social transformative potential was developed as they were capable of spreading health care information. In times of pandemic and confinement, children’s entertainment activities are of great value, especially when they provide important knowledge that helps preventing COVID-19 and so many other infectious diseases.